Squamous odontogenic tumor: A rare tumor of premolar region of mandible: a case report - Salem, Suzan; Alamri, Rana; Saad, Islam (International Journal of Dental Research, 2018)
Background: The squamous odontogenic tumor is characterized as an extremely uncommon amiable neoplasm, beginning from the rests of Malassez, gingival surface epithelium or from remainders of the dental lamina. The squamous odontogenic tumor was first described by Pullon et al. (1975), since that time only 50 cases in the English-language literature in which the microscopic characteristics are frequently very well demonstrated. The characteristic radiographic appearance is that of a triangular shaped unilocular radiolucency associated with the roots of erupted teeth and has a predilection for the anterior maxilla and the posterior mandible.Methods: We reported a case of squamous odontogenic tumor occurring in a 40-year-old female in the premolar are of mandible with common localization and appearance. The tumor underwent surgical excision for histopathological examination and confirming diagnosis, followed by total resection of the tumor and using demineralized freeze-dried bone allograft and collagen membrane to fill defect.Results: Histological examination revealed a proliferation of mature stratified squamous epithelial islands in a dense fibrous connective stroma and the diagnosis of squamous odontogenic tumor was confirmed.Conclusions: Although squamous odontogenic tumor is a rare tuomr which arise from the rest of Malassez, but it should be listed as a differential diagnosis and confirmed with histopathological examination, it should be treated first conservatively, but upon recurrence a more aggressive line of treatment is to be followed.